2014
DOI: 10.5430/crcp.v2n1p17
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic features of early stage gastric adenocarcinoma of fundic gland type (chief cell predominant type): a case report

Abstract: A 64-year-old Helicobacter pylori infection-naïve woman was found to have a small (≤ 10 mm) depression on the anterior wall of the upper gastric body. On white light endoscopy, the lesion appeared to be inconspicuous, whitish with dilated vessels. 0.2% indigo carmine chromoendoscopy enable better visualization of the depression. On narrow band imaging with magnification, the microsurface structure of the surrounding mucosa was absent and a network of tortuous microvessels were observed within the depressed are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…A review of studies on GA-FG-CCP published in English language indicates that 46 cases have been reported to date[4-16]. Almost all patients were Japanese, but a study by Singhi et al[9] in 2012 comprised 10 non-Asian patients, including Hispanics, Caucasians and African-Americans.…”
Section: Clinical Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…A review of studies on GA-FG-CCP published in English language indicates that 46 cases have been reported to date[4-16]. Almost all patients were Japanese, but a study by Singhi et al[9] in 2012 comprised 10 non-Asian patients, including Hispanics, Caucasians and African-Americans.…”
Section: Clinical Characteristicsmentioning
confidence: 99%
“…With respect to coloration, GA-FG-CCP is often covered with normal-colored or faded ( i.e ., whitish or yellowish) mucosa. Fujii et al[16] suggested that the faded appearance is caused by atrophy in the foveolar epithelium above cancer tubules, but not in the surrounding mucosa. Another characteristic of GA-FG-CCP is vasodilation on the tumor surface, which is attributed to the displacement of surface vessels by tumor tissue followed by congestion[13].…”
Section: Endoscopic Findingsmentioning
confidence: 99%
See 3 more Smart Citations